PEMBAHARUAN HUKUM PROSEDUR PENGEMBALIAN ASET TINDAK PIDANA - Santos, Ricardo; Gultom, Elfrida Ratnawati (Ensiklopedia Education Review, 2024)
The research aim is to explore the reform of legal procedures concerning the return of assets obtained through criminal activities in Indonesia. It examines the current legal framework and compares it with practices in other nations. The research employs descriptive normative methodology, analyzing secondary data qualitatively and drawing conclusions through deductive reasoning. Through analysis of concrete cases, evaluation of agreement terms documents, review of the arbitration process, and consideration of the social and cultural context, this research reveals the complexity of the legal matters arise. And through an in-depth analysis process, this research will explore the legal procedures for returning assets resulting from criminal acts. The research results found similarities and differences in the procedures and implementation of the two countries. In addition, this research provides suggestions for increasing effectiveness in returning assets that are outside the state's jurisdiction. This research hopefully can provide in-depth insight to legal practitioners, academics and other stakeholders to realizing a good legal system and supporting development.Keywords: Legal Reform, Procedure, Asset Recovery